2015
DOI: 10.1590/1807-3107bor-2015.vol29.0014
|View full text |Cite
|
Sign up to set email alerts
|

Dental fluorosis and its influence on children’s life

Abstract: This study verified the prevalence of dental fluorosis in 12-year-old children and its association with different fluoride levels in the public water supply, and evaluated the level of perception of dental fluorosis by the studied children. To assess fluorosis prevalence, clinical examinations were performed and a structured instrument was used to evaluate the self-perception of fluorosis. The water supply source in the children's area of residence since birth was used as the study criterion. In total, 496 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 15 publications
4
26
0
8
Order By: Relevance
“…33 It is also higher than that reported in literature, 34 38 Also in Argentina where, with similar fluoride content in water, DF prevalence is lower 39 than that reported in Mexican communities. So it might be pertinent to suggest a reevaluation of the concept of "optimal" fluoride concentration in water proposed in norm which should be revised given the fact nowadays multiple sources of fluoride exist and may be used or misused when combined involuntarily.…”
Section: Prevalence Of Fluorosis In Mexicomentioning
confidence: 81%
“…33 It is also higher than that reported in literature, 34 38 Also in Argentina where, with similar fluoride content in water, DF prevalence is lower 39 than that reported in Mexican communities. So it might be pertinent to suggest a reevaluation of the concept of "optimal" fluoride concentration in water proposed in norm which should be revised given the fact nowadays multiple sources of fluoride exist and may be used or misused when combined involuntarily.…”
Section: Prevalence Of Fluorosis In Mexicomentioning
confidence: 81%
“…Otros estudios realizados en los últimos años en el país, utilizando también el índice de Dean reportaron altas prevalencias del problema en población en edad escolar (22,23); situación que ha sido también reportada por otros países de la región (24)(25)(26)(27)(28). Así mismo, los resultados publicados recientemente del cuarto estudio Nacional de Salud bucal -ENSAB IV, reportan prevalencias de fluorosis dental de 65% y 56% en los niños de 12 y 15 años; respectivamente (29).…”
Section: Discussionunclassified
“…It should be noted that the included sample lived in an area of endemic fluorosis. A study in Brazil showed an association between the presence of fluorosis and areas with excessive fluoride in the water supply (23). Thus, the presence of negative impact can be especially important for individuals living in areas with naturally fluoridated at above-optimal levels (24).…”
Section: Discussionmentioning
confidence: 99%